Oral health problems among school children in rural area: a cross-sectional study - C. S., Jayalekshmi; Birajdar, Shrikant S.; C., Keerthana; Gurav, Ravindra B. (International Journal Of Community Medicine And Public Health, 2024)
Background: Students are the wealth of the nation as they constitute one of the important segments of the population. The foundation of good health and sound mind is laid during the school age period. During this period, they are vulnerable to various oral health problems. These conditions are the hurdles in their physical, mental, emotional, and social development. In view of this, a study was conducted to assess the oral health status of the school students in rural areas. Methods: Cross-sectional study was conducted in rural area among school children in the month of March 2023. Standard proforma was used to record the data related to oral morbidity among the subjects. Data entry and statistical analysis was done with the help of Microsoft Excel. ꭓ2 and SE (p1-p2) tests were used to compare difference in categorical variables. The statistical level of significance was fixed at p<0.05. Results: 432 students were examined. 226 (52.31%) subjects were having oral morbidity. 151 (66.81%) subjects in the age group of 5-10 years while 75 (33.19%) in the age group of >10-16 years were having oral health problems (p<0.05). 155 (59.73%) students from primary section and 71 (40.27%) students from secondary section were suffering from oral morbidity (p<0.05). Dental caries was observed among 194 (44.91%) subjects followed by mouth ulcers (09.72%). 143 (53.36%) underweight subjects were suffering from dental caries (p<0.05). Conclusions: Common oral health problems found in school going children can be addressed with the implementation of school health program in effective way. These common infirmities can be prevented by actively involving parents and teachers in school health services.